Correction: Induced pluripotent stem cell-derived monocytic cell lines from a NOMID patient serve as a screening platform for modulating NLRP3 inflammasome activity. - Ryosuke Seki; Akira Ohta; Akira Niwa; Yoshinori Sugimine; Haruna Naito; Tatsutoshi Nakahata; Megumu K Saito (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0237030.].